Dermal fibroblast-derived extracellular matrix (ECM) synergizes with keratinocytes in promoting re-epithelization and scarless healing of skin wounds: Towards optimized skin tissue engineering - Xiangyu Dong; Han Xiang; Jiajia Li; Ailing Hao; Hao Wang; Yannian Gou; Aohua Li; Saidur Rahaman; Yiheng Qiu; Jiahao Li; Ou Mei; Jiamin Zhong; et al. (Bioactive Materials)
Skin serves as the first-order protective barrier against the environment and any significant disruptions in skin integrity must be promptly restored. Despite significant advances in therapeutic strategies, effective management of large chronic skin wounds remains a clinical challenge. Dermal fibroblasts are the primary cell type responsible for remodeling the extracellular matrix (ECM) in wound healing. Here, we investigated whether ECM derived from exogenous fibroblasts, in combination with keratinocytes, promoted scarless cutaneous wound healing. To overcome the limited lifespan of primary dermal fibroblasts, we established reversibly immortalized mouse dermal fibroblasts (imDFs), which were non-tumorigenic, expressed dermal fibroblast markers, and were responsive to TGF-β1 stimulation. The decellularized ECM prepared from both imDFs and primary dermal fibroblasts shared similar expression profiles of extracellular matrix proteins and promoted the proliferation of keratinocyte (iKera) cells. The imDFs-derived ECM solicited no local immune response. While the ECM and to a lesser extent imDFs enhanced skin wound healing with excessive fibrosis, a combination of imDFs-derived ECM and iKera cells effectively promoted the re-epithelization and scarless healing of full-thickness skin wounds. These findings strongly suggest that dermal fibroblast-derived ECM, not fibroblasts themselves, may synergize with keratinocytes in regulating scarless healing and re-epithelialization of skin wounds. Given its low immunogenic nature, imDFs-derived ECM should be a valuable resource of skin-specific biomaterial for wound healing and skin tissue engineering.